PENGEMBANGAN KEBUN WISATA PENDIDIKAN (KWP) UNNES MELALUI BIOEDUENTERPREUNERSHIP - Rahayuningsih, Margareta; Abdullah, Muh; Arifin, Samsul; N, Vitradesi (Indonesian Journal of Conservation, 2016)
Educational garden of Semarang State University has an area of about two hectares and developed since 2001. Initial management focuses on developing Jelajah Alam Sekitar (JAS) (exploring environment around). The potential of Unnes basically can be used as inventory for the campus environment, and therefore could be used as branding of Conservation University through creative and innovative products with the concept of empowerment. The purpose of this activity is the development and sustainability of the program in Educational Gardens of Unnes through Biodeduenterpreneurship. IbIKK Development of Educational Gardens of Unnes as Conservation University branding through the Bioeduenterpreunership has formed a business unit under the name "Omah Keboen Unnes", draw up a business plan , develop tour packages, education and training, and has been able to improve the infrastructure and services by adding completeness of equipment and facility improvements. With the promotion that is conducted recently, a business unit Omah Keboen Unnes in 2014 has been able to attract consumers with details of 15 people follow the package â€œKetanâ€ (Paket Tulang Daung [Package of Bone Leaf]), 100 people follow package JAS to know the biodiversity in KWP, 200 students attend the package outbound and also 60 training plant nursery.Â Kebun Wisata Pendidikan Unnes (Universitas Negeri Semarang) memiliki luas sekitar dua hektar dan dikembangkan sejak tahun 2001. Awal pengelolaan lebih fokus untuk mengembangkan pendidikan jelajah alam sekitar (JAS). Potensi yang dimiliki Unnes tersebut pada dasarnya dapat dijadikan sebagai inventaris bagi lingkungan kampus dan selanjutnya dapat dijadikan sebagai branding Universitas Konservasi melalui produk kreatif dan inovatif dengan konsep pemberdayaan. Tujuan kegiatan ini adalah pengembangan dan keberlanjutan program di Kebun Wisata Pendidikan Unnes melalui Biodeduenterpreneurship. IbIKK Pengembangan Kebun Wisata Pendidikan Unnes sebagai Branding Universitas Konservasi melalui program Bioeduenterpreunership telah membentuk unit usaha dengan nama â€œOmah Keboen Unnesâ€, menyusun business plan yang terperinci, mengembangkan paket-paket wisata, pendidikan dan pelatihan, serta telah dapat meningkatkan prasarana dan layanan dengan menambah kelengkapan peralatan dan pembenahan fasilitas. Dengan promosi yang belum lama dilakukan, unit usaha Omah Keboen Unnes pada tahun 2014 telah mampu menarik konsumen dengan rincian 15 orang mengikuti paket Ketan (Paket Tulang Daun), 100 orang mengikuti paket JAS untuk mengenal keanekaragaman hayati di KWP, 200 siswa mengikuti paket outbond dan juga 60 orang mengikuti pelatihan pembibitan tanaman.Â